การทดสอบการแพ้ยาทางผิวหนัง และการตรวจไซโตไคน์ที่หลั่งจากเม็ดเลือดขาวที่มีความจำเพาะกับยา โดยวิธีอิไลสปอตในการวินิจฉัยการแพ้ยาเซฟาโลสปอรินชนิดเฉียบพลัน - บุญธร ตันวรเศรษฐี (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Background: Cephalosporins are commonly prescribed nowadays and the prevalence of non-immediate hypersensitivity reactions to cephalosporins has increased worldwide. No practical method to diagnose cephalosporin hypersensitivity is currently available.Objective : This study was to compare the in vivo and in vitro testing methods for the diagnosis of non-immediate hypersensitivity reactions to cephalosporins.Methods : Skin tests and ELISPOT assay were performed in 28 patients with a history of nonimmediate hypersensitivity reaction to cephalosporins.Results : Skin tests and ELISPOT assays yielded positive results in 2 and 10 patients with a history of non-immediate hypersensitivity reactions to cephalosporins. The sensitivity of ELIPOT assays was significantly higher than that of skin tests (35.7% versus 7.1%, p=0.008). Nonculprit drug (other betalactam) reaction determined by ELISPOT assays was 25%.Conclusion : ELISPOT assays might be useful methods to diagnose non-immediate hypersensitivity reactions to cephalosporins in clinical practice.